2019
DOI: 10.1177/0197918319844176
|View full text |Cite
|
Sign up to set email alerts
|

To Europe or Not to Europe? Migration and Public Support for Joining the European Union in the Western Balkans

Abstract: For decades, countries aspiring to join the European Union (EU) have been linked to it through migration. Yet little is known about how migration affects individual support for joining the EU in prospective member states. We explore the relationship between migration and support for EU accession in the Western Balkans. Using data from the Gallup Balkan Monitor survey, we find that prospective and return migrants, as well as people with relatives abroad, are more likely to vote favorably in a hypothetical EU re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Future researchers must, thus, look more closely at personal or familial migration experiences. Such experiences, as publicopinion research in the Balkans by Ivlevs and King (2020) has shown, can have a robust effect on whether an individual supports regional integration. This article did not investigate how migration desires may have influenced attitudes toward free movement in the AU.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Future researchers must, thus, look more closely at personal or familial migration experiences. Such experiences, as publicopinion research in the Balkans by Ivlevs and King (2020) has shown, can have a robust effect on whether an individual supports regional integration. This article did not investigate how migration desires may have influenced attitudes toward free movement in the AU.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the findings confirm the work of Lutz (2021), who argued that attitudes toward foreigners undermine support for free movement, shedding new light on the negative implications of anti-immigration attitudes in the AU. Fourth, the analysis identified key determinants of citizen opinion on free movement (e.g., state fragility and linguistic fractionalization) that were previously ignored by Eurocentric public-opinion scholarship on regional integration (e.g., Toshkov and Kortenska 2015; Ferrera and Pellegata 2018; Vasilopoulou and Talving 2019; Ivlevs and King 2020). This article’s results, and their implications for how scholars understand public attitudes toward visa liberalization, are discussed in more detail below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations